2016
DOI: 10.1080/19490976.2016.1239681
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of endothelial cells during perturbation of the gut vascular barrier

Abstract: It has been widely demonstrated that tolerance against gut microbiota is compartmentalized to mucosal sites where microbes mostly reside. How the commensal bacteria are excluded from the entrance into the blood stream via intestinal capillaries that are located beneath the gut epithelium was not clear. We recently described the existence of a new anatomical structure, the 'gut vascular barrier' (GVB), both in murine and human intestines that plays a fundamental role in avoiding indiscriminate trafficking of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 40 publications
1
53
0
5
Order By: Relevance
“…Recently, Spadoni et al have confirmed the existence of GVB with the morphological and functional characteristics resembling to the blood brain barrier in murine and human intestines that plays a key role in avoiding indiscriminate trafficking of bacteria from the gut into bloodstream, and the vascular barrier integrity can be altered by Salmonella typhimurium via the modulation of the Wnt/beta-catenin pathway [34]. Thus, the alteration of gut capillary influences GVB [2]. The murine CLP procedure is a classical model of sepsis, which may adversely influence GVB.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Recently, Spadoni et al have confirmed the existence of GVB with the morphological and functional characteristics resembling to the blood brain barrier in murine and human intestines that plays a key role in avoiding indiscriminate trafficking of bacteria from the gut into bloodstream, and the vascular barrier integrity can be altered by Salmonella typhimurium via the modulation of the Wnt/beta-catenin pathway [34]. Thus, the alteration of gut capillary influences GVB [2]. The murine CLP procedure is a classical model of sepsis, which may adversely influence GVB.…”
Section: Discussionmentioning
confidence: 85%
“…Spadoni et al have demonstrated that Salmonella typhimurium is capable of inhibiting the activation of Wnt/beta-catenin pathway [2,34]. This signaling has been reported elsewhere to exert the anti-inflammatory or pro-inflammatory properties [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations